EFFECTS OF PROCESSING METHODS ON SNAIL (Achatina achatina) MEAT YIELD AND SENSORY QUALITY - Osobase, C.; Ilaboya, I. I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the effect of blanching, unblanching, curing, and smoke drying on snail (Achatina achatina) meat yield and quality. A total of 20kg of snail was bought from the market and was processed by blanching or unblanching, and their shell, meat, and waste weights were recorded. Equal weights of snail meat were subjected to curing (with and without spices) in 5% salt solution and subsequently smoke-dried. Sensory evaluation was carried out using a 9-point hedonic scale. Results showed that unblanched snails yielded approximately 6% more meat than blanched snails. However, blanching reduced mucous secretion, facilitated processing and produced meat with a more stable shelf-life. Smoke drying reduced meat weight across all treatments, with retention levels of 40% (control), 30% (cured with spices), and 32% (cured without spices). Sensory evaluation indicated that spiced samples were rated highest in taste, flavor, juiciness, tenderness, and appearance, followed by unspiced samples, while the control rated lowest. Statistical analysis confirmed significant differences at both 1% (P< 0.01) and 5% (P< 0.05) levels. It was concluded that blanching is the preferred processing method due to its ease and improved hygiene, while smoke drying remains a practical preservation technique for long-term storage and export. The addition of local spices (nutmeg, onion, thyme, grains of paradise) enhanced flavor and consumer acceptance of smoke-dried snail meat.